2006
DOI: 10.1038/sj.eye.6702351
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal intraocular pressure profiles and progression of chronic open-angle glaucoma

Abstract: Purpose To evaluate whether the amplitude of day-and-night intraocular pressure (IOP) profiles influences the rate of progression of chronic open-angle glaucoma. Methods The hospital-based clinical observational study included day-and-night profiles of IOP measurements performed on 458 patients (855 eyes) with chronic open-angle glaucoma or ocular hypertension. The 24-h pressure profiles obtained by Goldmann applanation tonometry contained measurements at 0700, noon, 1700, 2100, and midnight. Results In the wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 16 publications
0
30
0
1
Order By: Relevance
“…In one study, Asrani et al concluded that the diurnal IOP range was a significant risk factor for glaucoma progression 16. However, a subsequent report by Jonas et al showed no statistically significant association between progression and IOP amplitude; a subgroup analysis for 174 NTG eyes showing that progression of NTG was associated instead with the minimum and mean IOPs 17. Interestingly, in the present study, as many as 43.0% (34/79) of treated eyes attained at least a 20% reduction in minimum IOP, and 22.8% (18/79) attained at least a 30% reduction.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, Asrani et al concluded that the diurnal IOP range was a significant risk factor for glaucoma progression 16. However, a subsequent report by Jonas et al showed no statistically significant association between progression and IOP amplitude; a subgroup analysis for 174 NTG eyes showing that progression of NTG was associated instead with the minimum and mean IOPs 17. Interestingly, in the present study, as many as 43.0% (34/79) of treated eyes attained at least a 20% reduction in minimum IOP, and 22.8% (18/79) attained at least a 30% reduction.…”
Section: Discussionmentioning
confidence: 99%
“…These results are not consistent with other studies investigating the role of peak IOP established with single IOP measurements over a long-term follow-up, in which peak IOP was not found to be an independent risk factor for progression. [41][42][43] To date only one previous study 44 analyzed retrospectively the effect of 24-hour peak IOP on long-term progression in POAG. In that study 24-hour peak IOP was documented to be an independent risk factor for progression, and a 24-hour peak IOP below 18 mm Hg ensured a 78% nonprogression rate in treated POAG patients after 5 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Others, however, have failed to find similar associations. 43 Consequently, the importance of 24-hour IOP parameters in glaucoma remains an area of controversy even among glaucoma experts. 57 …”
Section: A Evidence For the Role Of Short-term Iop Variation In Glaumentioning
confidence: 99%
“…Jonas et al 43 performed a retrospective chart review of 855 eyes from 458 treated patients with normal tension glaucoma (NTG), POAG, or ocular hypertension. They investigated the potential association of 24-hour IOP parameters with disease progression after a mean follow-up of almost 56 months.…”
Section: Circadian Iop Variations In Treated Eyesmentioning
confidence: 99%